Low-fat, lactose-free and leucine-enriched chocolate cow milk prototype: A preliminary study on sensorial acceptability and gastrointestinal complaints following exhaustive exercise - Cristiano D. da Silva; Dirce R. de Oliveira; Ítalo T. Perrone; Carlos H. Fonseca; Emerson S. Garcia (Taylor & Francis Group, 2021)
Background Chocolate milk has gained recent scientific support as a recovery drink. However, it is known that high exercise-demand triggers gastrointestinal discomfort which continues post-exercise, thereby hindering this nutritional strategy. In addition, those who are lactose intolerant cannot benefit from a milk-based beverage. Thus, the aim of this preliminary study was to develop a low-fat, lactose-free, and leucine-enriched chocolate cow milk prototype (CML) representing nutrition-related recommendations for football players, as well as assess athletes' individual subjective outcomes for gastrointestinal complaints and sensorial acceptability in a field-based setting following strenuous team-sport physical demands. Methods This study followed a single group and repeated-measured design with 10 football players (23 ± 2 yrs., 74 ± 14 kg, 174 ± 5 cm) who consumed CML following a 90-min football match simulation protocol (FMP). The total CML intake to achieve 0.150 g leucine·kg [BW]·h− 1 occurred in aliquots of 50, 30 and 20% at 0-, 45- and 75-min post-FMP, respectively. Athletes were evaluated by the prevalence, the type and severity (bloating, nausea, flatulence, and gastric reflux) of gastrointestinal complaints and sensorial acceptability (overall perception, appearance, consistency, and flavour) after drinking each aliquot in a 4-h recovery period. Results The CML showed higher scores for "Product Acceptability Index" (88%) and sensorial acceptability (~ 8 in 9-point hedonic scale). Kendall's W with bootstrapped resample (95%CI) revealed agreement among respondents as "moderate" (overall perception, flavour) to "strong" (appearance, consistency) and with no significant agreement differences between rater response in the timeline analysis (0.57 up to 0.87; p > 0.05). Agresti-Caffo add-4 analysis (95% confidence interval, [95%CI]) revealed no differences in each time-point analysis versus baseline for athletes classified as having severe gastrointestinal symptoms, but confirmed concern with bloating (three athletes showed a transient response at 2-h and only one continued until 3-h; p = 0.051). Conclusions These preliminary findings suggest that CML presents good taste and high acceptability by the sampled athletes. Thus, CML may be an alternative sport drink for immediate post-workout supplementation to overcome the energy deficit, offer co-ingested leucine, maintain palatability and adherence including lactose intolerance following a team sport-specific fatigue. Trial registration RBR-2vmpz9, 10/12/2019, retrospectively registered.